2004
DOI: 10.1016/s0014-5793(04)00156-5
|View full text |Cite
|
Sign up to set email alerts
|

Glucosylceramides in Colletotrichum gloeosporioides are involved in the differentiation of conidia into mycelial cells

Abstract: Glucosylceramides (GlcCer) were extracted from the plant pathogen Colletotrichum gloeosporioides and puri¢ed by several chromatographic steps. By using electrospray ionization mass spectrometry and nuclear magnetic resonance, GlcCer from C. gloeosporioides were identi¢ed asMonoclonal antibodies against these structures were produced and used as tools for the evaluation of the role of GlcCer in the morphological transition of C. gloeosporioides. In the presence of antibodies to GlcCer, the di¡erentiation of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
65
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 33 publications
6
65
0
3
Order By: Relevance
“…For instance, Fonsecaea pedrosoi and Colletotrichum gloeosporioides treated with antibodies against GlcCer showed reduced growth and conidia germination. Interestingly, treatment with these antibodies enhanced macrophage activity, suggesting a possible role on stimulating host cells against fungi [19,20]. This is supported by studies in Pseudallescheria/Scedosporium complex, where it was also shown that antibodies against GlcCer are able to inhibit conidia germination and to enhance phagocytosis by macrophages, as well as being able to present a synergic effect with itraconazole [22].…”
Section: Sphingolipids As Targets For Treatment Of Fungal Infections mentioning
confidence: 67%
See 1 more Smart Citation
“…For instance, Fonsecaea pedrosoi and Colletotrichum gloeosporioides treated with antibodies against GlcCer showed reduced growth and conidia germination. Interestingly, treatment with these antibodies enhanced macrophage activity, suggesting a possible role on stimulating host cells against fungi [19,20]. This is supported by studies in Pseudallescheria/Scedosporium complex, where it was also shown that antibodies against GlcCer are able to inhibit conidia germination and to enhance phagocytosis by macrophages, as well as being able to present a synergic effect with itraconazole [22].…”
Section: Sphingolipids As Targets For Treatment Of Fungal Infections mentioning
confidence: 67%
“…Several natural inhibitors of fungal GlcCer synthesis have been described to exhibit a potent antifungal activity [16][17][18]. In addition, monoclonal antibodies against GlcCer are able to inhibit the growth of different fungi, including C. neoformans, Colletotrichum gloeosporioides, Fonsecaea pedrosoi, Pseudallescheria boydii and Scedosporium apiospermum [19][20][21][22][23].…”
mentioning
confidence: 99%
“…Sera from healthy individuals with no previous laboratory exposure to F. pedrosoi were also collected and tested against the same preparation by ELISA. Alternatively, a monoclonal anti-CMH antibody (12 g/ml, starting dilution) was used as a probe to detect CMH (9,22). After washing in TBS, an alkaline phosphatase-labeled goat anti-mouse or anti-human immunoglobulin was added (1:5,000), followed by incubation for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…F. pedrosoi sclerotic cells (2 ϫ 10 2 ) were suspended in 100 l of PBS supplemented with antibodies to CMH in concentrations varying to 1.5 to 100 g/ml. In this range of concentrations, antibodies to CMH were demonstrated to be inhibitory for different fungal species (9,(21)(22)(23). Cell suspensions were then incubated in the presence of antibodies to CMH for 8 h at 28°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation